Excellent outcomes and lack of prognostic impact of cell of origin for localized diffuse large B‐cell lymphoma in the rituximab era. (12th October 2015) - Kumar, Anita; Lunning, Matthew A.; Zhang, Zhigang; Migliacci, Jocelyn C.; Moskowitz, Craig H.; Zelenetz, Andrew D.
Summary: Therapeutic options for limited‐stage diffuse large B cell lymphoma (DLBCL) include short‐ or full‐course R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone) ± radiotherapy. The optimal treatment remains unclear. The prognostic value of cell‐of‐origin (COO) in early stage DLBCL is unknown. Patients with limited‐stage DLBCL (stage I or stage II, non‐bulky) treated with R‐CHOP ± involved field radiotherapy (IFRT) from 1999 to 2012 were included. COO by the Hans algorithm was analysed in a subset of patients. Of 261 patients, 30% were stage I ( N  = 82), 37% stage IE ( N  = 96), <1% stage IXEE ( N  = 1), 18% stage II ( N  = 46) and 14% stage IIE ( N  = 37). The stage‐modified International Prognostic Index stratified patients into prognostically relevant groups. There was no significant difference in progression‐free survival (PFS) or overall survival (OS) for patients in the germinal centre B‐cell‐like (GCB; n  = 65) and non‐GCB cohorts ( n  = 22). Seventeen patients received R‐CHOP × 3–4 cycles (Arm A), 147 received R‐CHOP × 3–4 cycles + IFRT (Arm B), 48 received R‐CHOP × 6 cycles (Arm C), and 50 received R‐CHOP × 6 cycles + IFRT (Arm D). The outcomes were excellent, with 5‐year PFS of 82% and 5‐year OS of 93%, and were similar across the 4 treatment groups. In the rituximab era, outcomes for limited‐stage DLBCL, regardless of treatment approach, were excellent. Baseline COO was not a significant prognostic factor in patients treated with short‐course R‐CHOP + IFRT.